A Systematic Feasibility Analysis of User Interfaces for Illiterate Users: A Systematic Feasibility Analysis of User Interfaces for Illiterate Users - Jan, Sadeeq; Maqsood, Imran; Ahmad , Iftikhar; Ashraf, Majid; Khan, Fazal Qudus; Khalil, Muhammad Imran Khan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Literacy is conventionally defined as the ability to read and write simple statements. Illiteracy and poor education are major problems in developing countries. In this digital era, computers can play a vital role in improving literacy. However, computer illiteracy is also high in developing countries and their citizens cannot understand the complex digital User Interfaces. Research shows that User Interface (UI) design should be different for illiterate, semi-illiterate and literate users. Furthermore, the design should also consider the cultural context like language, culturally relevant images, etc. The researchers of Human Computer Interaction for Development (HCI4D) face challenges to improve literacy to design effective and usable interfaces. HCI4D researchers have designed such interfaces for illiterate users over the years. Their major findings were to use non-textual designs over text-based interfaces. In the non-textual designs, they further considered artifacts like sounds, images, icons, backgrounds etc. This paper systematically reviews the work carried out by HCI4D researchers in four different domains i.e. health, agriculture, e-commerce, and education. We have extracted User Interface (UI) design recommendations from the related literature for UI designers of these domains. We believe this could help designers to create effective design interfaces for illiterate population in the domains considered for review